Ictal gamma-band interactions localize ictogenic nodes of the epileptic network in focal cortical dysplasia - Janca, Radek; Jahodova, Alena; Hlinka, Jaroslav; Jezdik, Petr; Svobodova, Lenka; Kudr, Martin; Kalina, Adam; Marusic, Petr; Krsek, Pavel; Jiruska, Premysl (Clinical neurophysiology, 2021)
OBJECTIVE: Epilepsy surgery fails in > 30% of patients with focal cortical dysplasia (FCD). The seizure persistence after surgery can be attributed to the inability to precisely localize the tissue with an endogenous potential to generate seizures. In this study, we aimed to identify the critical components of the epileptic network that were actively involved in seizure genesis. METHODS: The directed transfer function was applied to intracranial EEG recordings and the effective connectivity was determined with a high temporal and frequency resolution. Pre-ictal network properties were compared with ictal epochs to identify regions actively generating ictal activity and discriminate them from the areas of propagation. RESULTS: Analysis of 276 seizures from 30 patients revealed the existence of a seizure-related network reconfiguration in the gamma-band (25-170 Hz; p < 0.005) - ictogenic nodes. Unlike seizure onset zone, resecting the majority of ictogenic nodes correlated with favorable outcomes (p < 0.012). CONCLUSION: The prerequisite to successful epilepsy surgery is the accurate identification of brain areas from which seizures arise. We show that in FCD-related epilepsy, gamma-band network markers can reliably identify and distinguish ictogenic areas in macroelectrode recordings, improve intracranial EEG interpretation and better delineate the epileptogenic zone. SIGNIFICANCE: Ictogenic nodes localize the critical parts of the epileptogenic tissue and increase the diagnostic yield of intracranial evaluation.
Keywords: gama rytmus EEG; Humans; lidé středního věku; Nerve Net; dítě; malformace mozkové kůry; Child; Drug Resistant Epilepsy; Female; mladý dospělý; dospělí; lidé; mozková kůra; Malformations of Cortical Development; Cerebral Cortex; Adult; refrakterní epilepsie; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Adolescent; Gamma Rhythm; Young Adult; retrospektivní studie; nervová síť; mužské pohlaví; následné studie; mladiství